IMPACT OF MIXED DIETARY VITAMIN E-SELENIUM POWDER ON REPRODUCTIVE HORMONES' CONCENTRATION OF MALES AND FEMALES IN JAPANESE QUAIL BIRD (COTURNIX COTURNIX JAPONICA) - Mahmood Amen; Mohammed Wahhab; Sarmad Muhammad; Shahab Gezh (Mesopotamia Journal of Agriculture)
The Study’s goal was to show the effect of dietary supplementation of mixed vitamin E and Selenium powder (Sodium selenite) in Japanese quail on reproductive hormone levels. The study was conducted on a total number of (128) Japanese quail birds at 12 weeks old. The experimental birds were randomly divided into four groups (32birds /group), each group had eight replicates (1male/3 females /replicate). The four experimental diets were: T1= (Basal diet (control), T2= (vitamin E-Selenium powder 1.0 gm/kg of basal diet), T3= vitamin E-Selenium powder 1.5 gm/kg of basal diet) and T4 (vitamin E-Selenium powder 2.0 gm/kg of basal diet). The results indicated that adding vitamin E and selenium to diet (T4) significantly (P≤0.05) increased the level of plasma concentrations of Estradiol (E2), testosterone and progesterone as compared with the control group(T1) in male and female of Japanese quail. In concerned with the male group the T4 supplemented diet increased the Testosterone level significantly. There was no significant difference for the T2 and T3 in the level of testosterone and Estradiol compared to the control. Although the T2, T3 and T4 diet decreased the level of progesterone hormone significantly. There is a significant decrease of progesterone for the T3 and T4 compared to the control and T2, which lastly do not differ from the control in the female groups.  It was clear that the supplemented diet with vitamin E and Selenium statistically (P<0.05) affected some reproductive hormones. So, it was recommended to perform further advanced, related, and specific nutritional studies through which accurate levels of minerals and trace minerals as supplementations will be added to the basal feed of various bird and animal species in order to increase both reproductive and productive aspects.